If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(u+8)=-7u-26
We move all terms to the left:
-4(u+8)-(-7u-26)=0
We multiply parentheses
-4u-(-7u-26)-32=0
We get rid of parentheses
-4u+7u+26-32=0
We add all the numbers together, and all the variables
3u-6=0
We move all terms containing u to the left, all other terms to the right
3u=6
u=6/3
u=2
| 16y+4=8 | | 2(x-5)-5=-3(-4x+9)-x | | 2(3x-5)+3x=8 | | 5y^-60=5y | | 20=12+-2s | | 4x-+3(x-2)=21 | | -5p+8=38 | | x3-4x2+1=0 | | 9x+80=x+40 | | 4(x+8)=-6(3x-5)+6x | | 5/2x=10/x+2 | | 3z+10=9 | | 5^2x=200 | | -34=-8x+5(x-5) | | 5n-13=n+7 | | x/0.25x+1.5=3.5 | | 12x^2-288x+1296=0 | | 3x/2+5=2x | | |2x-11|=3 | | 32=12=4(z-1) | | 3(x-1)=5(2x-1) | | 4k+5-2k=3k+1 | | 15=2x-11 | | 1.5/12=18/x | | -7b^2+b=8 | | 4v-11=65 | | 10z=2 | | 4.9x-7.5=21.9 | | 7+12z-6=7z+49-3z | | 3x-40=x+15 | | 4x+20x25=0 | | u/2+17=39 |